Implementasi Peraturan Bupati Bima Nomor 37 Tahun 2020 terhadap Keefektifan Kesadaran Masyarakat dalam Mematuhi Protokol Kesehatan Covid19 di Kabupaten Bima - Kadarusman; Muslimah; Abdurrasyid; Firzhal Arzhi Jiwantara (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Disciplinary policies and law enforcement of health protocols are policies formalized by the government in preventing and controlling COVID-19. Bima Regent Regulation Number 37 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an effort to prevent and control Corona Virus Disease 2019. The implementation of Discipline and Law Enforcement of Health Protocols is a regulation ratified by the Regent of Bima as an effort to control the spread of COVID-19 in Bima Regency. . This type of research uses descriptive qualitative. The results of this study indicate that the implementation of the implementation of health protocols in Bima Regency has been carried out properly because the community already knows the rules for implementing and enforcing health protocols and knowing the importance of implementing health protocols. Research results Public compliance with health protocols is quite good and the application of health protocols in the Bima Regency area is in accordance with the Bima Regent Regulation Number 37 of 2020 concerning the Implementation of Discipline and Law Enforcement of Health Protocols as an Efforts to Prevent and Control Corona Virus Disease 2019.